THE ANATOMICAL CHARACTERS OF Ampelocissus (Vitaceae) IN SUMATRA - Syadwina Hamama Dalimunthe; Tatik Chikmawati; Elizabeth A. Widjaja (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2020)
The revision of Ampelocissus was performed by observing the anatomical character of Ampelocissus leaves. The leaves were collected from 33 collection numbers of Herbarium Bogoriense (BO) and four collection numbers from Sumatra exploration. The purpose of this study is to update the information of diversity and to support species concept delimitation of Ampelocissus based on the anatomical study, especially on the sterile plant. Anatomical characters were observed on nine species and one variety of Sumatran Ampelocissus. Ampelocissus species is varied by the anatomical characters, i.e.: shape of the anticlinal wall of abaxial and adaxial epidermal cell, number of palisade layers, upper epidermal cell thickness, leaf thickness, presence of papillae on stomata neighboring cell, type, and shape of calcium oxalate crystals, also stomata position. The cluster analysis of Ampelocissus in Sumatra based on 16 anatomical characters showed the coefficient similarity in the range of 0.48 - 0.81. The research showed that the leaf anatomical characters can be used as additional characters to distinguish the species of Ampelocissus. Keywords: calcium oxalate crystals, diversity, papillae, similarity coefficient, species concept   ABSTRAK Ciri Anatomi Ampelocissus (Vitaceae) di Sumatera Revisi Ampelocissus dilakukan dengan mengamati ciri anatomi daun dari marga Ampelocissus. Sebanyak 33 nomor koleksi Herbarium Bogoriense (BO) dan empat nomor koleksi hasil eksplorasi di Sumatera digunakan. Penelitian ini bertujuan untuk memperbarui informasi mengenai keanekaragaman dan mendukung konsep jenis Ampelocissus berdasarkan ciri anatomi, terutama pada tumbuhan steril. Studi anatomi dilakukan pada sembilan jenis dan satu varietas Ampelocissus di Sumatera. Jenis-jenis Ampelocissus di Sumatera bervariasi pada ciri anatomi yaitu bentuk dinding antilkinal sel epidermis pada bagian abaksial dan adaksial, jumlah lapisan jaringan tiang, ketebalan sel epidermis atas, ketebalan daun, kehadiran papila, jenis dan bentuk kristal kalsium oksalat, serta posisi stomata terhadap sel epidermis pada bagian abaksial daun. Analisis pengelompokan Ampelocissus di Sumatera menggunakan 16 ciri antomi dan menghasilkan fenogram dengan koefisien kemiripan 0,48 - 0,81. Ciri anatomi daun dapat digunakan sebagai ciri tambahan yang memiliki nilai taksonomi dalam membedakan jenis-jenis Ampelocissus di Sumatera.